First vertebrate assemblage of the Early Holocene from northeastern Argentina (Mesopotamian Region) - Peralta, Matias Javier (2024)
In this contribution, we report and describe a microvertebrate fossil assemblage recovered from a Holocene fluvial unit located in Entre Ríos Province, northeastern Argentina (Mesopotamian Region). The analyzed stratigraphic section is on the left bank of Doll creek (32° 18’ 24” S, 60° 25’ 41” W), southwestern Entre Ríos Province. The stratigraphic section was divided into three levels and a total of 36 samples were collected. Radiocarbon dating was obtained from gastropod shells from the base of the section, with a range of 9,990±140 BP (Early Holocene). It was possible to record fishes, such as eels and characids, anurans, reptiles, birds, and small-medium size mammals. Most of the identified taxa constitute the first fossil records from the Quaternary of the Mesopotamian Region and even from Argentina. The systematic, biostratigraphic, and taphonomical results show that the environmental conditions in this area at the beginning of the Holocene period were similar to the current ones: a temperate-humid climate with water availability. This contribution is the first study of a microvertebrate fossil assemblage from the Early Holocene from northeastern Argentina (Mesopotamian Region) and represents an important contribution to the knowledge of the Quaternary fossil vertebrates from Argentina.